Spatiotemporal Changes of Land Use, Land Surface Temperature and Urban Heat Island in Bogura District Using Multispectral Satellite Images - Md Rashidul Islam; Md Bodruddoza Mia; Md Nasif Jamil; Masuma Chowdhury; ASM Woobaidullah (Journal of the Asiatic Society of Bangladesh, Science, 2025)
This study presents an in-depth analysis of the spatiotemporal changes in land use/land cover (LULC) land surface temperature (LST) and urban heat islands (UHI) in Bogura District, with a focus on Bogura Municipality, utilizing multispectral satellite images from 1993 to 2023. The LULC of supervised classification identified significant shifts, including a sharp expansion of settlement areas, particularly by 2023, and a notable increase in vegetation cover, reflecting improved vegetation health. However, agricultural and fallow lands have shown a marked decline, especially post-2000, suggesting shifts in land use or a reduction in vegetation density. Water bodies have gradually decreased in areas, likely due to land conversion or the drying up of sources. The normalized difference vegetation index (NDVI) analysis corroborates these findings, highlighting fluctuations in vegetation health and coverage. Concurrently, LST analysis reveals an increase in higher temperature categories, closely linked to urbanization and the formation of urban heat islands (UHIs). The expansion of settlement areas has intensified the UHI effect, where urban zones exhibit significantly higher temperatures compared to surrounding rural areas. Additionally, areas of low temperature have expanded, indicating changes in land surface characteristics. The data underscores the dynamic nature of land use changes over the three-decade period, with urbanization and land cover alterations significantly impacting both vegetation and surface temperatures in the region. The study provides a framework for creating plans to counteract the negative effects of climate change, especially the UHI effect, and to direct sustainable urban planning. J. Asiat. Soc. Bangladesh, Sci. 51(1): 19-38, June 2025